K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 4 2023

\(xy-\left(x+2y\right)=3\)
\(xy-x-2y=3\)
\(y\left(x-2\right)-x=3\)
\(y\left(x-2\right)-x+2=3+2\)
\(y\left(x-2\right)-\left(x-2\right)=5\)
\(\left(y-1\right)\left(x-2\right)=5\)
Ta có bảng sau:

\(y-1\)\(1\)\(5\)\(-1\)\(-5\)
\(x-2\)\(5\)\(1\)\(-5\)\(-1\)
\(y\)\(2\)\(6\)\(0\)\(-4\)
\(x\)\(7\)\(3\)\(-3\)\(1\)

Vậy các cặp \(\left(x;y\right)\) là \(\left(7;2\right);\left(3;6\right);\left(-3;0\right);\left(1;-4\right)\)

=>xy-x-2y=3

=>x(y-1)-2y+2=5

=>(x-2)(y-1)=5

=>\(\left(x-2;y-1\right)\in\left\{\left(1;5\right);\left(5;1\right);\left(-1;-5\right);\left(-5;-1\right)\right\}\)

=>\(\left(x,y\right)\in\left\{\left(3;6\right);\left(7;3\right);\left(1;-4\right);\left(-3;0\right)\right\}\)